Radiographic determination of pelvic limb orthopaedic measurements in maned wolf (Chrysocyon brachyurus) - Siqueira, Rafael C.; Rahal, Sheila C.; Inamassu, Leticia R.; Mamprim, Maria J.; Teixeira, Rodrigo H. F.; Teixeira, Carlos R.; Rassy, Fabricio B.; Mesquita, Luciane R.; Monteiro, Frederico O. B.; Felix, Marcilio; Melchert, Alessandra (Wiley, 2018)
The aim of this study was to determine some radiographic reference values for hip joint, femur and patella in maned wolves. Ten maned wolves (Chrysocyon brachyurus), five live (G1) and five cadavers (G2), were used. There were no statistically significant differences in the radiological measurements between right and left pelvic limbs of the G1 and G2, except for mechanical lateral proximal femoral angle (mLPFA) in both Groups. The comparison of the measurements between Groups showed difference only for mechanical lateral distal femoral angle (mLDFA). Norberg angle values were 113.1° and 112.9° for G1 and G2. The values of femoral angle of inclination by Hauptman A and Hauptman B methods were 139.7° and 128.6° for G1, and 139.3° and 128.7° for G2. Femoral varus angle values were 5.5° for G1 and 3.9° for G2. The values of anatomic lateral distal femoral angle and anatomic lateral proximal femoral angle were 96.8° and 95.2° for G1, and 95.0° and 95.6° for G2. The values of mLDFA for G1 and G2 were 96.5° and 95.7°. The values of mLPFA were 95.8 (right) and 93.5 (left) for G1, and 95.7 (right) and 93.8 (left) for G2. The values of patellar ligament length, patellar length and L:P ratio were 4.6, 2.4 cm and 1.9 for G1, and 4.4, 2.3 cm and 1.8 for G2. In conclusion, the radiographic reference values described for the hip joint, the femur and the patella, may be useful in the diagnosis of diseases and deformities in maned wolves.